Factors contributing to morning rain in the upper Río Chagres Basin, Panamá - Ishizaki, Noriko N.; Nakaegawa, Tosiyuki; Pinzón, Reinhardt; Sasaki, Hidetaka (Frontiers in Earth Science, 2023)
The Upper Chagres River Basin plays an important role in the stable operation of the Panama Canal. Previous study has shown that there is a salient regional difference in diurnal variation of precipitation in the basin. Precipitation during the rainy season peaks in the early afternoon throughout the basin, but precipitation is also observed in morning at sites located in the northern part of the basin. However, the cause has not been clarified due to limitation of ground observation number. To tackle this issue, we conducted dynamical downscaling experiments with horizontal grid spacing of 5 and 2 km, nested in a global atmospheric model with horizontal grid spacing of about 20 km. The results showed that the 2-km convection-permitting model successfully reproduced the regional differences of observed diurnal variations. Downscaled results indicated that intensified low-level northeasterly winds over the southern Caribbean Sea triggered the favorable conditions for morning rain with the orographic effect under the seaside coastal regime in the western Caribbean Sea. This is in contrast to precipitation peaks in the early afternoon under the landside coastal regime.